A fundamental control performance limit for a class of positive nonlinear systems. (September 2018) - Goodwin, Graham C.; Carrasco, Diego S.; Seron, Maria M.; Medioli, Adrian M.
Abstract: A fundamental performance limit is derived for a class of positive nonlinear systems. The performance limit describes the achievable output response in the presence of a positive disturbance and subject to a sign constraint on the allowable input. An explicit optimal input is derived which minimises the maximum output response whilst ensuring that the minimum output response does not fall below a pre-specified lower bound. The result provides a fundamental performance standard against which all control policies, including closed loop schemes, can be compared. Implications of the result are examined in the context of blood glucose regulation for Type 1 Diabetes.